Endovascular therapy of carotid artery stenosis: a prospective case study. (4th December 2009) - Claus, D; Huppert, P; Bauersachs, R; Diegel, H; Hedtmann, G
Abstract : Carotid artery stenting was carried out in a prospective consecutive case study. All interventions were done by the same investigator (PH), and one type of stenting device was used. Additionally, periprocedural monitoring was carried out for at least 24 h. 190 patients were included (70±8.9 years). All had a high grade stenosis (>70% according to North American Symptomatic Carotid Endarterectomy Trial (NASCET) criteria). 140 were men and 50 were women. 104 (55%) had symptomatic stenosis and 86 (45%) had asymptomatic stenosis. A self-expanding nitinol–carotis stent was used (Cordis Precise stent; Johnson and Johnson) with an emboli capture guidewire basket system (Angioguard; Cordis). 30 day complications (infarct, hemorrhage, death due to either) were seen in 13 cases (6.8%). Disabling complications with an increase in the modified Rankin Scale by >2 points after 6 months were seen in five cases (2.6%). The rate of complications after carotid artery stenting was comparable with that after carotid endarterectomy (from the literature). No correlation was seen between complications and age, gender, diabetes, hypertension, symptomatic stenosis or plaque morphology. This may be because of the the 24 h post-procedural monitoring.